Climate Change, Agriculture, & Gender Dynamics: A Case Study of Campesinos in the Piedras River Watershed - Marsala-Bell, S. (2014)
Our objectives were developed in consultation with CIAT and included establishing a strong relationship with local stakeholders and campesinos in the city of Popayán and in the Piedras River Watershed and collecting preliminary data on farming strategies, farmer perceptions regarding climate change, and how gendered roles play a part in their perceptions of climate change. This information was important to CIAT/ CCAFS since they had chosen the Piedras River Watershed as a new project site in Colombia and they wanted to see if it was feasible to disseminate knowledge on climate-smart agricultural practices in the region. Our research constitutes a case study of farming practices in the Piedras River Watershed. One of our main results is that 33 out of 35 participants in our study knew of and had heard about climate change. Their main understanding of climate change was with respect to climate variability. Climate variability refers to the way climate fluctuates yearly, either above or below a long-term average.